A Chemically Synthesized Resveratrol Dimer is a Potent Inhibitor of Vascular Endothelial Growth Factor (VEGF) - Lin, Shengying; Guo, Maggie Suisui; Tang, Roy Wai-Lun; Ye, Yutong; HO, Yuen Man; Duan, Ran; Leung, Ka Wing; Zhou, Jianlong; Dong, Tina Ting-Xia; Tsim, Karl Wah-Keung (Archives of Clinical and Biomedical Research, 2026)
Vascular endothelial growth factor (VEGF) plays a critical role in angiogenesis, influencing various physiological and pathological processes. Indeed, the inhibitors of VEGF have been developed as angiogenic medications, e.g. bevacizumab (avastin). Here, we aim to explore the synthesis and evaluation of a novel resveratrol dimer, named RE-16, as a potential anti-VEGF agent. By structural modifications of resveratrol, RE- 16 was synthesized using a chemical linker to dimerize the resveratrol scaffold, resulting in a compound with improved binding affinity to VEGF, as compared to its parent compound. The binding assays of RE-16 to VEGF, including ultrafiltration and Biacore surface plasmon resonance (SPR), demonstrated the superior affinity of RE-16 in comparing to resveratrol. In line with this physical binding, the biological evaluations using human umbilical vein endothelial cells (HUVECs) revealed that the treatment of RE-16 effectively inhibited the VEGF-mediated biological activities in dosedependent manners, exhibiting better potency than the parental molecule– resveratrol. The favourable ADMET properties of RE-16 were also predicted through computational analysis, suggesting good intestinal absorption and low toxicity. Overall, RE-16 demonstrates promising potential as a therapeutic agent for the VEGF-mediated diseases, warranting further pharmacological development and clinical investigation.